Pengaruh Infrastruktur Terhadap Pertumbuhan Ekonomi Di Indonesia - Laila Hasyim Tambun; Delin Sea; Muhammad Zulfikar; Puti Andiny; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this paper is to determine the effect of roads on economic growth and to determine the effect of electricity on economic growth in Indonesia. This research uses Multiple Linear Regression analysis techniques. This type of research is quantitative descriptive. This type of data is secondary data. The results of this research show that road infrastructure has a probability value of 0.0858 > 0.05, so it can be concluded that road infrastructure has an influence but is not significant on Indonesia's economic growth. The probability value for electricity infrastructure is 0.0728 < 0.05, so it can be concluded that electricity infrastructure has an influence but is not significant on Indonesia's economic growth. This research uses data for 20 years, namely from 2003-2023.